Sonography of the renal and urinary bladder in horses - Durmus, AS; Han, MC (Indian Veterinary Journal, 2005)
Ultrasonography has been one of the principal imaging techniques used in veterinary practice. Ultrasonographic evaluation of the horse kidneys can be performed from the left and right body wall. The ultrasonographic evaluation of the horse urinary bladder should include a through transrectal evaluation (Reef, 1991). The aim of this study was to perform a sonographic examination of kidneys and urinary bladder of Thoroughbred English horses.